Intracellular compartmentation of troponin T: release kinetics after global ischemia and calcium paradox in the isolated perfused rat heart - Remppis, Bjoern-Andrew; Scheffold, Thomas; Greten, Henry Johannes; Haass, Markus; Greten, Tobias; Kübler, Wolfgang; Katus, Hugo (Journal of molecular and cellular cardiology, 1995)
A. Remppis, T. Scheffold, J. Greten, M. Haas, T. Greten, W. Kübler and H. A. Katus. Intracellular Compartmentation of Troponin T: Release Kinetics After Global Ischemia and Calcium Paradox in the Perfused Rat Heart. Journal of Molecular and Cellular Cardiology (1995) 27, 793-803. The marked differences in troponin T serum concentrations observed in patients with reperfused and non-reperfused myocardial infarction may be due to a perfusion dependent wash-out of an unbound fraction of cardiac troponin T. To test the release kinetics of troponin T experimentally, the isolated rat heart (Langendorff preparation) was damaged either by the calcium paradox or by no-flow ischemia. Following membrane damage by the calcium paradox troponin T (TNT) showed the same release kinetics in the coronary effluent as the cytosolic markers creatine kinase (CK) or lactate dehydrogenase (LDH). Peak levels of troponin T (282 ± 58 μg/l), CK (6754 ± 1642 U/l), and LDH (5817 ± 1730 U/l) occurred 5 min after onset of reperfusion with calcium containing buffers and returned to 9.9%, 1.3%, and 1% of their respective peak levels within 55 min of reperfusion. During reperfusion after no-flow ischemia different release kinetics were found for cytosolic enzymes and troponin T. After 60 min of ischemia, troponin T levels in the coronary effluent increased over the entire reperfusion period of 55 min, almost doubling the 5 min value (191%). In contrast, cardiac enzymes rapidly declined to 18% (CK) and 23% (LDH) of their respective 5 min values at the end of reperfusion. Light microscopy after reperfusion with carbon black revealed a complete and homogenous reperfusion of Langendorff hearts after no-flow ischemia. Immunoblot analysis confirmed the release of an undegraded 39 kDa troponin T molecule, both after global ischemia and the calcium paradox. These data indicate that prolonged ischemia induces a continuous liberation of cardiac troponin T, most probably from disintegrating myofibres, whereas membrane damage leads almost exclusively to leakage of a functionally unbound troponin T pool. These findings may explain the biphasic serum concentration changes of cardiac troponin T in patients with reperfused myocardial infarction.
Elektronische Reproduktion der Druck-Ausgabe 9. September 2004
Gesehen am 12.05.2025